Old Meany Hall from across campus, University of Washington, July 1965
Meany Hall was built in 1908 to serve as the auditorium for the Alaska-Yukon-Pacific Exposition. It was demolished in 1965 after suffering extensive damage in an earthquake. Typed on verso: Meany Hall, July 1965. Filed in: UW - Meany Hall (Old) (#463).